THE CORELATION BETWEEN STRESS LEVELS AND MENSTRUAL CYCLES IN STUDENTS OF STIKES MEDISTRA INDONESIA BEKASI - Nadzifa, Amalia; Santosa, Puji Raharja; Dedu, Baltasar S.S (Rena Cipta Mandiri, 2022)
This study discusses the menstrual cycle that occurs in female students caused by several factors. Factors associated with menstrual cycle disorders such as stress, physical activity, and diet. During stress, activation of the hypothalamic-pituitary-adrenal axis together with the autonomic nervous system can cause several changes, namely in the reproductive system, namely abnormal menstrual cycles. Students are a group that is prone to experiencing stress due to the responsibilities and demands of academic life on students. The research method used is quantitative with cross sectional and simple random sampling. The population is STIKes Medistra Indonesia students in 2022 with a sample of 129 female students. With the results of the study, it was found that p was 0.0000 so that the conclusion was that there was a relationship between stress levels and the menstrual cycle in female students of STIKes Medistra Indonesia Bekasi.